Peranan Saluran Komunikasi Massa dalam Upaya Menekan Peredaran Berita Hoaks di Masyarakat - Ahmad Husein; Masrona Harahap; Khoirunnas Adlani; Syarief Mulia Siregar; Siti Fadilah; Winda Kustiawan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to describe how mass communication channels can play a role in suppressing the circulation of hoaxes in society. The scope of this research covers the mass communication channels that exist in Indonesia, starting from the mass media and their types, to how they are used in tackling the rise of hoaxes. The research method used is a literature study of writings in books, journals, scientific articles, and previous research reports. The results obtained from this study, the mass media can suppress the circulation of hoaxes in society with various advantages and capacities of the mass media. In conclusion, mass communication channels play an important role in determining the information received and trusted by the public.